A novel loss-of-function mutation of GATA3 (p.R299Q) in a Japanese family with Hypoparathyroidism, Deafness, and Renal Dysplasia (HDR) syndrome. Issue 1 (December 2015) - Okawa, Tetsuji; Yoshida, Masanori; Usui, Takeshi; Kudou, Takahiro; Iwasaki, Yasumasa; Fukuoka, Kazuki; Takahashi, Norio; Uehara, Yuka; Oiso, Yutaka
Abstract Background Hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome is a rare autosomal dominant disorder caused by mutations in the zinc finger transcription factor gene, GATA3 . GATA3 has 2 zinc finger domains, which play an important role in the increase in target gene transcription activity. Case presentation A 50-year-old woman and her 27-year-old daughter were followed up because of hypoparathyroidism. They had bilateral sensorineural deafness. Abdominal computed tomography scanning revealed renal dysplasia in the mother, but no renal anomaly in the daughter. Direct sequencing ofGATA3 gene revealed a novel heterozygous missense mutation at codon 299 (p.R299Q) in exon 4. This mutation is located at the junction between the 2 zinc fingers. The structure prediction showed that it caused a conformation change in this junction area, affecting the spatial position of the zinc fingers. Additionally, a more marked conformation change was observed in the N-terminal zinc finger region compared to that in the C-terminal region. Functional analysis of this mutant protein using anin vitro luciferase reporter assay system confirmed that the mutation abolished the enhancing effects of wild-type GATA3 on the promoter activity of the consensus GATA responsive element and that of humanPTH gene. Conclusion We identified a novel R299Q mutation inGATA3 in a Japanese family with HDR syndrome. We confirmed that R299Q is a loss-of-function mutation, due to the extensive conformational change in the zinc fingers of GATA3.